Continuous Opinion Dynamics in Complex Networks (Communications in Computational Physics, 2009)
Many realistic social networks share some universal characteristic properties, such as the small-world effects and the heterogeneous distribution of connectivitydegree, which affect the dynamics in society system, especially the opinion dynamicsin society. To see this, we study the opinion dynamics of the Improved Deffuant Model(IDM) in complex networks. When the two opinions differ by less than the confidenceparameter ϵ (0